Campus Bullying and Mental Health of Queer People in China - Xu, Yingnan (Transactions on Social Science, Education and Humanities Research, 2024)
The survey aimed to investigate targeted bullying in public schools in inland China and to gain an overview of the negative school issues faced by lgbtq+ students in schools. Campus bullying is a vicious negative behavior on campus, and today, it is also a huge hidden danger and problem affecting society and even adolescents’ mental health. Additionally, studies have demonstrated that lesbian, gay, bisexual, and transgender (LGBT) students tend to experience more mental health challenges than their heterosexual and gender-conforming peers, with increased suicide attempts, lower self-esteem, and higher rates of depression. National studies have revealed that college students often possess negative and conservative views towards LGBT groups, leading to social stigma, discrimination, and violence for homosexuals, accompanied by varying degrees of emotional disorders, substance dependence, suicide, and other issues. LGBT students face a higher prevalence of homophobic bullying in schools compared to their heterosexual counterparts. Homophobia refers to a negative belief, attitude, stereotype, and behavior towards the LGBT community, which directly influences the bullying of LGBT students on campus, i.e., homophobic bullying. Bullying is a form of repeated aggression by powerful individuals against vulnerable individuals, affecting the physical and mental health of children and adolescents.